The use of technology for arts-based activities in older adults living with mild cognitive impairment or dementia: A scoping review. (January 2023) - MacRitchie, Jennifer; Floridou, Georgia A.; Christensen, Justin; Timmers, Renee; de Witte, Luc
For older adults living with mild cognitive impairment or dementia, creative arts-based activities can offer many benefits from enjoyment as leisure/recreation to an avenue to maintain cognitive, social and emotional wellbeing. With growing interest and recognition that technology could have potential to assist in delivering these activities in more accessible and personalised ways, a scoping review was undertaken to systematically examine the scientific literature for technology-assisted creative arts activities for older adults living with dementia. We searched PubMed, PsychINFO, Web of Science, Scopus and ACM Digital Library databases using keywords centering on population with dementia, an intervention using technology, and a context of creative arts, with no restrictions on the type of outcome measured. We retrieved 3739 records, with an additional 22 from hand-searching. 51 full-text articles met the inclusion and exclusion criteria. Findings of the review indicate technologies principally being designed for music activities (listening, and music-making), as well as storytelling and visual arts. The majority of devices were custom-made, with studies mainly reporting on validating the success of the device/intervention. This suggests most work in the field is currently at prototyping stage, although a few devices are now commercially available. Recommendations for future research includes involvement of participants reporting on their previous experiences in the arts and how this influences co-design choices, and inclusion of different severities of dementia in the participant/co-design group. Furthering device development past prototyping stage as well as collaboration between teams would enable comparisons to be made across different types of devices used for the same activity, and comparisons across arts-based activities that could lead to cross-disciplinary outcomes for the design of creative arts-based assistive technologies.